ANTIHYPERTENSIVE POTENTIAL OF CHAYOTE FRUIT EXTRACT FOR HYPERTENSION TREATMENT - Nadila, Fadia (Majority, 2014)
Abstract Hypertension is defined as systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg. The prevalence of hypertension keep increasing. In Indonesia, the highest prevalence is in the province of Bangka belitung. Treatment of hypertension generally takes a long time, safety and side effects of long-term drugs use are major concerns, so that herbal medicine become one of an alternative choice. One of the plants used as antihypertensive is chayote fruit (Sechium edule), especially the fruit and the rind. The active compound in chayote fruit that used as antihypertensive is flavonoid that can inhibit angiotensin I converting enzyme (ACE) and diuretic. Chayote fruit extracts can be used as an alternative treatment of hypertension. Keywords: chayote fruit, flavonoid, hypertension Abstrak Hipertensi didefinisikan tekanan darah sistolik ≥140 mmHg dan diastolik ≥90 mmHg. Prevalensi hipertensi semakin meningkat. Di Indonesia prevalensi tertinggi pada provinsi Bangka belitung. Penatalaksanaan hipertensi umumnya membutuhkan waktu yang lama, faktor keamanan dan efek samping penggunaan obat jangka panjang menjadi perhatian utama, sehingga obat herbal menjadi pilihan alternatif. Salah satu tanaman yang digunakan sebagai antihipertensi adalah buah labu siam (Sechium edule), terutama buah dan kulit buah. Senyawa aktif dalam buah labu siam yang berfungsi sebagai antihipertensi adalah flavonoid yang dapat menghambat angiotensin I converting enzyme (ACE) dan sebagai diuretik. Ekstrak buah labu siam dapat dijadikan alternatif pengobatan hipertensi. Kata kunci: flavonoid, hipertensi, labu siam